Strategi Pelatihan Teater Kompas MAN 1 Nganjuk dalam Pengembangan Literasi, Karakter, dan Soft Skill Siswa di Madrasah di Era Digital - Vadyas Andrean Saputra; Indar Sabri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research aims to analyze in depth the extracurricular training strategies of Teater Kompas at MAN 1 Nganjuk as an educational model for developing students' literacy, character, and soft skills. This phenomenon is particularly compelling to study due to its ability to harmonize theatrical arts within a formal religious-based educational environment. The research methodology employed is descriptive qualitative with a case study approach. Data collection was conducted through observation, in-depth interviews with the theater coach and members, and documentation of activity portfolios. The results indicate that Teater Kompas implements systematic training strategies by adapting the management styles and training techniques of Teater Gandrik and various national theater figures. The training process integrates physical, vocal, and emotional exercises while ensuring the theatrical practices remain compliant with applicable religious regulations. Managerially, the organization demonstrates proficient resource and financial management. The impact and achievements are evident in national-level awards and the strategic roles members hold within school organizations such as the OSIS and MPK. Furthermore, this research highlights that the religious constraints inherent in a madrasah-pesantren environment do not serve as barriers, but rather as catalysts for creative innovation that shape professional character in students.